2001
DOI: 10.1103/physrevb.64.092408
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent memory effects in the bilayer manganite(La0.4Pr0.6)<

Abstract: We report on the low-temperature resistance and magnetization of a single crystal of the bilayer manganite (La 0.4 Pr 0.6 ) 1.2 Sr 1.8 Mn 2 O 7 . In zero field the sample is an insulator at all temperatures while at fields larger than 3 T a transition to a ferromagnetic metallic state is observed. Below 50 K the sample shows a pronounced memory effect, in which both resistivity and magnetization become dependent on the magnetic history and clearly demonstrate hysteretic behavior. At these low temperatures a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
7
22
0
Order By: Relevance
“…51 Above 50 K, relaxation effects are more rapid. 29 Here, the phase diagram from both optics (which measures the microscopic nature of the charge degrees of freedom) and magnetization are in good agreement, although the boundary becomes more diffuse with increasing temperature (inset, Fig. 6(a)).…”
Section: B Optical Phase Diagramsupporting
confidence: 51%
See 2 more Smart Citations
“…51 Above 50 K, relaxation effects are more rapid. 29 Here, the phase diagram from both optics (which measures the microscopic nature of the charge degrees of freedom) and magnetization are in good agreement, although the boundary becomes more diffuse with increasing temperature (inset, Fig. 6(a)).…”
Section: B Optical Phase Diagramsupporting
confidence: 51%
“…57 For comparison, we also plotted several points determined from selected resistivity, magnetization, and magnetostriction measurements. 29,31,51 Magnetization measurements indicate two boundaries at ∼2 and 5 T below 50 K, perhaps due to domain rotation. 51 Above 50 K, relaxation effects are more rapid.…”
Section: B Optical Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…However, a magnetic field could induce a field-induced first-order paramagnetic insulator to ferromagnetic metal transition in this latter compound. In addition, a huge decrease of the c-axis resistivity by a factor of 1 ϫ 10 6 was observed at T = 5 K in the presence of a magnetic field of 5 T. 5,6 The firstorder transition was also accompanied by a remarkable negative magnetoresistance when the field was oriented along the c axis, indicating the presence of an important interplay between spin, carrier, and orbital degrees of freedom. 7,8 A polarized neutron study of this compound revealed an increase in the population of the d͑3z 2 − r 2 ͒ orbitals of Mn 3+ in the field-induced ferromagnetic state when the field was along the c axis.…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, the decrease of the average angle of the Mn-O-Mn bond in the 1 1 0 direction is correlated with a decrease of the molecular magnetization (Tables 2 and 3). By substituting the smaller Nd or Sm cations for La, it can be supposed that the MnO 6 octahedra are elongated on the c axis, favouring the d 3z 2 −r 2 orbital of Mn 3+ [19]. This leads to a decrease of the FM interaction that can result in destruction of the FM state [19].…”
Section: Chemical Compositionmentioning
confidence: 97%